Comparison of mesa and device diameter variation in double wafer-fused multi quantum-well, long-wavelength, vertical cavity surface emitting lasers - Menon .P.S,; Kandiah .K,; Majlis .B.Y,; Shaari .S, (Universiti Kebangsaan Malaysia, 2011)
Long-wavelength vertical-cavity surface-emitting lasers (LW-VCSELs) have profound advantages compared to traditional edge-emitting lasers offering improved properties with respect to mode selectivity, fibre coupling, threshold currents and integration into 2D arrays or with other electronic devices. Its commercialization is gaining momentum as the local and access network in optical communication system expand. Numerical modeling of LW-VCSEL utilizing wafer-fused InP-based multi-quantum wells (MQW) and GaAs-based distributed Bragg reflectors (DBRs) is presented in this paper. Emphasis is on the device and mesa/pillar diameter design parameter comparison and its effect on the device characteristics.